Analysis of the Implementation of Good Corporate Governance on Company Performance (Case Study of Hotel Madani Medan) - Daffa Baihaqi Purnomo; Dara Puspita; Khoirul Ardani Manurung; Juliana Nasution (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is to determine the application of gcg in relation to improving performance at Madani Medan hotels. This is due to good corporate governance which aims to prevent and correct significant errors. This study used a qualitative research method with a descriptive approach. Data were obtained by interviewing managers and hotel staff and document analysis.The results of this study indicate that the GCG principle can increase the performance of Madani hotels. At the time of transparency, it can be increased by creating a hotel web page that has an effect on increased load performance. Another effect is the increase in room occupancy, so that operational performance can be improved. The next effect is that it can help Madani hotels get financing funds that are relatively cheap because creditors believe in the rate of return of funds. So that with decreased production costs, it will affect the increased financial performance. In an effort to realize justice with the opportunity given to all employees in expressing their opinions. This helps increase employee productivity which also increases operational performance..